e-lab Remote Laboratory Demonstration - Neto, R. B.; Fernandes, H. (International Journal of Online and Biomedical Engineering (iJOE), 2013)
e-lab is a remote laboratory infrastructure, powered by a software framework designed for distributed data collection, that allows to perform experiments and retrieve data from a remote apparatus. In this demonstration we will present the e-lab interface properties and its modus operandi, giving as well some topics of complimentary software use for data interpretation and analysis. An overview of e-labâ??s technical specifications will also be presented.